Efforts to Improve Elementary School Students' Conceptual Understanding in Islamic Education Learning by Implementing Role Playing Models - Hudia; Abubakar (Journal of Action Research in Islamic Education, 2025)
This study aims to improve elementary school students' conceptual understanding of Islamic education by implementing the role-playing model. This study is a classroom action research with the Kemmis & Mc Taggart model with four steps in each cycle: planning, action, observation, and reflection. The subjects of this study were fifth-grade students of Grong-Grong Pidie Elementary School. The research data were collected using observation and test techniques. Observation was used to obtain data on teacher and student learning activities, while tests were used to measure students' conceptual understanding of Islamic education. The collected data were then analyzed using descriptive statistical techniques. The results of the study indicate that the role-playing model can improve students' conceptual understanding of Islamic education in elementary schools. This is evident from the results of the analysis of the research data which show that the percentage of student completion experienced a significant increase in each cycle with details of 63.17% in the pre-cycle, then increased in cycle 1 to 78.24% and in cycle 2 to 86.17%. The average value achieved also increased with details of pre-cycle 70.19, cycle 1 obtained 82.33 and cycle 2 obtained 89.47. Furthermore, the results of the standard deviation test also showed that the standard deviation value in each cycle was getting smaller, meaning that the students' conceptual understanding ability was more evenly distributed. Based on these results, the role playing model can be used as an alternative learning model that can be used to overcome the low conceptual understanding ability of students in Islamic education learning in elementary schools.